Neuropsychological Study of Familial Alzheimer's Disease Caused by Mutation E280A in the Presenilin 1 Gene (2003)
ABSTRACT: In Antioquia, Colombia, investigators have recently discovered the largest family with the E280A mutation in the presenilin 1 gene that causes one type of familial Alzheimer’s disease (FAD). The current study compares two groups within this family: those diagnosed with Alzheimer’s disease (AD) in its early stage (nine subjects) and relatives (carriers) who did not show any signs of dementia (nine subjects). A battery of the following neuropsychological tests was administered to subjects in both groups: the Consortium to Establish a Registry for Alzheimer’s Disease (CERAD), a Phonological Verbal Fluency test, the Visual “A” Cancellation Test, memory of three phrases, the Rey-Osterrieth Complex Figure, and the Trail Making Test Part A. Statistical analyses of the average test scores of each group showed that the AD group scored significantly (p< 0.01 or p < 0.05) lower on 29 of the 43 neuropsychological variables measured (67 percent). Therefore, this specific battery was useful in discriminating subjects with AD from their healthy relatives who are carriers of the disease. The AD group as a whole presented slight dementia with predominant deficits in memory, language, praxis, and attention. This profile is similar to those reported in subjects with sporadic AD in its early stage and confirms the findings found in other neuropsychological studies of subjects with FAD linked to mutations in chromosome 14.